What is the effect of advanced diagnostic methods on sensitivity and survival in the multiple breast cancers? A systematic analysis and comparison - Acar, Hasan Zafer; Ozer, Nazmi - (Asian Journal of Medical Sciences, 2021)
The sensitivities of the advanced diagnostic methods appear to be higher than the conventional methods and do have the potential to prolong survival, in multiple (multifocal and multicenter) breast cancers. Thus, the aim of this study is to compare the sensitivities of advanced and conventional diagnostic methods and to reveal their effects on survival. The studies published about diagnosis and treatment methods in multiple breast cancer in literature were searched, analyzed, and the sensitivities obtained with advanced and conventional diagnostic methods were compared, and the results were evaluated statistically. The sensitivity obtained with the advanced diagnostic methods in multiple breast cancers was found to be significantly higher than the conventional methods (p <0.05). The high sensitivities obtained with advanced diagnostic methods were found to have a high potential for survivial prolongation in multiple breast cancers. The use of advanced diagnostic methods in breast cancer screening programs, the investigation of tumor foci with molecular methods, increases the rate of diagnosis in multiple breast cancers. In the treatment of multiple breast cancers, a personalized treatment plan is made with the diagnosis of the molecular structure of the tumor foci. Thus, the recurrence rates are reduced, the survival is prolonged.